Precipitation as the main mechanism for Cd(II), Pb(II) and Zn(II) removal from aqueous solutions using natural and activated forms of red mud - da Conceição, Fabiano Tomazini [UNESP]; da Silva, Mariana Scicia Gabriel [UNESP]; Menegário, Amauri Antonio [UNESP]; Antunes, Maria Lucia Pereira [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP]; Fernandes, Alexandre Martins [UNESP]; Dorea, Caetano; Moruzzi, Rodrigo Braga [UNESP] (Elsevier, 2021)
The red mud (RM) has been used as an alternative low-cost adsorbent to remove trace elements, with the adsorption onto sodalite surface described as the main removal mechanism for trace elements. However, recent studies have shown that precipitation might be of great importance for some trace metals removal using natural and thermal activated RM. Therefore, the aim of this study was to identify the main mechanism responsible for Cd(II), Pb(II) and Zn(II) removal from aqueous solutions using natural and activated forms of RM, based on sequential extractions and a precipitation kinetic model was developed. Results showed that the carbonate fraction was responsible for the highest trace elements removal (ca. 85%), with the minerals assemblages precipitated: otavite – CdCO3, cerussite - PbCO3, smithsonite - ZnCO3 and anglesite - PbSO4. The kinetic model showed that the mineral precipitation was limit due to the HCO3− consumption during the formation of new minerals. Hence, this study showed that precipitation was the central mechanism on trace elements removal, regardless the natural or activated forms of RM. This finding raise doubt about the effectiveness of the traditional adsorption isotherms and kinetics models to describe trace metals removal using RM, contributing with new insights for future researches involving these hazardous materials.
Keywords: Brazilian red mud; Kinetics modelling; Sequential extraction; Trace elements